O gênero de horror nos quadrinhos brasileiros: linguagem, técnica e trabalho na consolidação de uma industria - 1950/1967 - Silva, Luciano Henrique Ferreira da (2012)
The first publications of horror comics edited by La Selva Publishing since 1950, started an publishing tradition that would last nearly 40 years in the Brazilian consume culture. The popularity of the horror genre in the Brazilian comics allowed the proliferation, survival and growth of many small publishers, mainly allocated on the suburbs of São Paulo. By the methods of importation and adaptation of editorial matter from La Selva Publishing , or because the search for emancipation and development of Brazilian artists by Outubro Publishing, the horror comics becomes an important material source to theoretical research about work practices, organization forms and methodology of Brazilian publishers from the 50’s and 60’s. Focusing the commercial exploitation of horror genre in these two decades, we will make a socio-historical approach of labor relashionship, production and consumption, in view of intermediation between different social groups involved in these processes. Correlating the interferences between language and technical codes among the media, we intend to demonstrate influences of media products and cultural industry to form new professional skills, methods and formats. Investigating the inheritance of methods, techniques and language of the legacy from the pulp fiction in pulp magazines, from which emerged new formats such as comic book and photo-romance magazines, we observe that the introduction of these new formats was caused by the need to change the choices of publishing towards massification. In this historical period of the consolidation of cultural industries and media convergence in the Brazilian cultural scene, we will compare the tradition of horror comics started by La Selva and Outubro, with the popularity of radio broadcast and motion picture film. In the filmography of José Mojica Marins and the popular character Zé do Caixão (Coffin Joe), we see a synthesis of the blend betwen technical language and the course of visual narrative, transported from comics to the movies, as the reuse of professionals related to the horror tradition in Brazilian comic. In the technical, discursive and socio-historical analysis about the selected works, we expose the vision of these social groups on technical development, and on the other hand, understand it as a result of interaction between multiple areas and social actors.